REKONSTRUKSI EPISTEMOLOGI PENDIDIKAN ISLAM BERBASIS SPIRIT INTEGRALISTIK - Akmal Mundiri (Universitas Nurul Jadid, 2018)
Historically Islamic Education has formulated two currents of thought which both take different forms either from the aspect of material, educational system, as well as in the institutional form. The two models are 1). models of Islamic education that has traditionalist pattern (easting) which in its development more emphasis on doctrinal-normative tend exclusive-apologetic . 2). Modernist Islamic education model (Western) which then in its development is considered losing its transcendent spirits. The emergence of current thinking on the duality model of Western-style Islamic education can not be denied as a result of the heat of the globalization and information era.Based on this condition, it takes a strong foundation for the study of the implementation of Islamic education in the form of integrative epistemology. Epistemology results logical consequences in the form of eliminating a paradigm of dichotomy between religious and general science, changes patterns of indoctrinated Islamic education into participatory patterns between teacher and pupil, substitutes ideological paradigm into a scientific paradigm which is based on the revelations of Allah, reconstructs secular and free spiritual values curriculum into curriculum based on monotheism, and change the approach from a theoretical or conceptual approach to the contextual approach.